All Days 2008
DOI: 10.2118/114124-ms
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous Carbonate Nucleation and Inhibition

Abstract: In this research, the nucleation kinetics and inhibition of ferrous carbonate (siderite) were investigated in a batch reactor under rigorously anoxic conditions in the absence of reducing agents. The nucleation kinetics of ferrous carbonate in 0.01 m NaCl solutions was measured from 25°C to 65°C at constant supersaturation. A decrease in temperature slows down ferrous carbonate nucleation rate. Similarly an increased ionic strength and a decreased saturation index result in a slower ferrous carbonate nucleatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Based on these results, it can be concluded that citrate is not only adsorbed on the surface of siderite with the (Fe 2+ citrate) − form but also incorporated into the siderite structure during siderite formation. The adsorption or incorporation of (Fe 2+ citrate) − can hinder the growth of siderite crystals, which may be due to surface poisoning or/and structural distortion [ 37 ]. When the citrate concentration is increased, these effects become stronger, causing the formation of smaller siderite crystals, which are covered by many (Fe 2+ citrate) − complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, it can be concluded that citrate is not only adsorbed on the surface of siderite with the (Fe 2+ citrate) − form but also incorporated into the siderite structure during siderite formation. The adsorption or incorporation of (Fe 2+ citrate) − can hinder the growth of siderite crystals, which may be due to surface poisoning or/and structural distortion [ 37 ]. When the citrate concentration is increased, these effects become stronger, causing the formation of smaller siderite crystals, which are covered by many (Fe 2+ citrate) − complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Citric acid (HOC(COOH)(CH 2 COOH) 2 ) is a common organic ligand in natural water and is also considered as a model compound for humic substances, having three carboxylic groups and one hydroxyl group [ 36 ]. While citrate inhibits the crystallization of carbonate minerals owing to the adsorption of citrate on the mineral surface [ 37 , 38 ], it is known to be incorporated into the structure of carbonates [ 38 , 39 ]. It is also known that this surface modification by organic functional groups (such as carboxylic ligands) can improve the reactivity of minerals [ 40 ] and thus be employed for developing a novel As(III) detector with high sensitivity [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reactive diffusion coefficient can be calculated through experimental data, such as provided by (Wang et al 2014) and (Yean et al 2008).…”
Section: Stage-4 Diffusion: Reactive Diffusion At Pipe Surfacementioning
confidence: 99%
“…15 Comparison between iron + carbonate ions and iron + sulfide ions kinetic reaction. Iron + carbonate ions kinetic reaction data are adopted from Yean et al (2008) and iron + sulfide ions from Wang et al (2014)…”
Section: St Distance (Ft)mentioning
confidence: 99%
“…Citrate is used widely as an iron-sequestering agent in the oil field. In addition to the formation of soluble Fe-citrate complexes, it was reported recently (Yean et al 2008) that citrate is able to act as a kinetic inhibitor for ferrous carbonate scale control. The effect of citrate on the performance of modified phosphonate inhibitors against calcium carbonate scale was also observed in the presence of 200 ppm Fe 2+ in this study.…”
Section: Static Bottlementioning
confidence: 99%